Nawal El-Saadawi: Membongkar Budaya Patriarkhi Melalui Sastra - Kulsum, Ummu (STAI Miftahul Ula Nganjuk, 2017)
Abstrak: Nawal el-Saadawi, an Egyptian feminist, which dismantle patriarchal culture in Egypt, through the work of the controversial novel